Educational Value in Erpangir Ku Lau Ritual with Gendang Lima Sendalanen - Ananta Prima Hasintongan (Jurnal Penelitian Humaniora, 2018)
This study was aimed at determining the Ritual Process in terms of the meaning and value contained in the Erpangir Ku Lau Ritual Ceremony and the presentation of the ethnic context of Gendang Lima Sendalanen, Batak Karo Ethnic. This type of research was descriptive qualitative with an ethnographic approach. This study was carried out in Semangat Gunung Village, Karo, North Sumatra. The informants of this study were Artists and Lecturers of Karo Batak traditional music at Medan State University, while the object of the research was Erpangir Ku Lau Ritual ceremony along with the accompaniment of the music of Gendang Lima Sendalanen. The data sources in this study were obtained through observation and documentation. The analysis technique consisted of data reduction and conclusions. The results showed that this Ceremony contained the meaning and value of Social and Cultural Education and Multicultural which were reflected in the lyrics of Oral Literature from the spells in ritual ceremonies hummed in a ritual song namely Mangmang which has the meaning of respecting the ancestors and purification of things things that are not good while the value of education in rituals is reflected in the effort to maintain the cultural heritage of the Erpangir Ku Lau ritual ceremony.Keywords: educational value, Ritual Erpangir Ku Lau, Gendang Lima Sendalanen